Moslem women’s participation in sustainable household clean water management: The case of Sekaran District - Annida Unnatiq Ulya (Center for Science and Technology, IAIN Surakarta, 2019)
Environment is easily changing through urban development and people's growth. In this situation, the availability of clean water would be threatened unless it has a good water management. The purpose of this research is to examine Moslem women’s participation in the sustainable household clean water management. This descriptive research analyses quantitative and qualitative data collected using questionnaire and interview towards 50 household women. The sampling methods employ accidental sampling in the Moslem community. This research has found that household clean water management has not been optimally done yet, so it could not perform the water use efficiency for environment and water sustainability although the women’s participation rate is high (75,40). In addition, the teaching of Islam has not emerged as the basic principle for water management by Moslem women in their household shown by the lack of sustainable water management practices.